Kohesi Gramatikal dan Makna Kontekstual pada Lirik Lagu Album Begadang Ciptaan H. Rhoma Irama - Hazwinda, Dita (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2018)
Music is not only about combination between tone and lyrics. If the combination is balance, the song will be qualified. Nowadays, music is not only about a right rhythm and melody, but the message as the song writer offers will be essential. The song writer must pay attention to the correlation between lyrics and contect which become a contectual meaning. The problem that raised in this research are 1) how the grammatical cohesion which contains in song Begadang from H. Rhoma Irama, 2) what kind of contectual which contain in the lyrics of this song Begadang from H. Rhoma Irama. This research is aimed to analyze element of grammatical cohesion and contectual meaning in lyric of Begadang song from H. Rhoma Irama. Descriptive, and qualititative orientation were used in this research. All of the lyrics of Begadang song became the data of this research. This research is motivated by kertarikan authors see mothers in households using facebook. A housewife is a married woman and her family work menajalankan ranging from cooking, taking care to clean the house